Techniques for Molecular Imaging Probe Design - Fred Reynolds; Kimberly A. Kelly (Molecular Imaging)
Molecular imaging allows clinicians to visualize disease-specific molecules, thereby providing relevant information in the diagnosis and treatment of patients. With advances in genomics and proteomics and underlying mechanisms of disease pathology, the number of targets identified has significantly outpaced the number of developed molecular imaging probes. There has been a concerted effort to bridge this gap with multidisciplinary efforts in chemistry, proteomics, physics, material science, and biology—all essential to progress in molecular imaging probe development. In this review, we discuss target selection, screening techniques, and probe optimization with the aim of developing clinically relevant molecularly targeted imaging agents.